The Impact of Caregiving Disruptions of Previously Institutionalized Children on Multiple Outcomes in Late Childhood. Issue 1 (8th October 2018) - Almas, Alisa N.; Papp, Leanna J.; Woodbury, Margaret R.; Nelson, Charles A.; Zeanah, Charles H.; Fox, Nathan A.
Abstract : This study examined disruptions in caregiving, as well as the association of these disruptions, with cognitive, behavioral, and social outcomes at age 12 in a sample of 136 Romanian children who were abandoned to institutions as infants and who experienced a range of subsequent types of care. Children were found to experience significantly more caregiving disruptions (CGD) earlier in life than later in childhood. More frequent CGD predicted increases in externalizing and internalizing behavior problems at age 12. Results are discussed in terms of the association between CGD and the long‐term development of children who have experienced institutional rearing.